2003
DOI: 10.1081/ese-120016929
|View full text |Cite
|
Sign up to set email alerts
|

Acute Toxicity of Some Heavy Metals toLatescalcariferFry with a Note on Its Histopathological Manifestations

Abstract: Static bioassay tests for acute toxicity of four heavy metals to fry of the fish Lates calcarifer in brackishwater medium were conducted. The 96 h LC50 values of metals such as Hg, Cu, Cr, and Mn for two different size groups 11 +/- 3 mm and 24 +/- 4 mm were found to be 0.085, 1.3, 27.9, and 220 mg/L and 0.20, 1.8, 33, and 250 mg/L, respectively. The rank order of toxicity of metals was found to be Hg > Cu > Cr > Mn. Using the safe concentration factor of 0.01, the allowable safe concentration for Hg, Cu, Cr, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
6

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 10 publications
2
10
0
6
Order By: Relevance
“…In contrast to embryo studies, significantly more work has been reported on the histopathology of mercury in older fish (Hammerschmidt et al, 2002;Ribeiro et al, 2002;Drevnick and Sandheirich, 2003;Krishnani et al, 2003). Several of the histopathological effects of MeHg on the fathead minnow reported in the current study have also been noted by the author in embryos of the coho salmon and rainbow trout Mottet, 1991, 1992).…”
Section: Embryo Pathologysupporting
confidence: 47%
“…In contrast to embryo studies, significantly more work has been reported on the histopathology of mercury in older fish (Hammerschmidt et al, 2002;Ribeiro et al, 2002;Drevnick and Sandheirich, 2003;Krishnani et al, 2003). Several of the histopathological effects of MeHg on the fathead minnow reported in the current study have also been noted by the author in embryos of the coho salmon and rainbow trout Mottet, 1991, 1992).…”
Section: Embryo Pathologysupporting
confidence: 47%
“…In euryhaline killifish Fundulus heteroclitus (96-h LC50: 18 mg Cu/L in freshwater and 294 mg Cu/L in 35% seawater) and topsmelt Atherinops affinis (168-h LC50: 44, 72, 134, and 205 mg Cu/L in 10, 17, 25, and 34% waters, respectively), larvae also became less sensitive to Cu as salinity increased [22,23]. In the present study, the 96-h LC50 for red sea bream larvae was 0.13 mg Cu/L, which falls within the reported values for other marine fish larvae [10,[19][20][21]. Copper toxicity in fish at ELS is substantially affected by salinity.…”
Section: Acute Toxicity Of Coppersupporting
confidence: 83%
“…Under similar experimental conditions, the 96-h LC50 values of Cu for a large majority of the reported freshwater fish larvae varied remarkably from 3.4 mg Cu/L for Chinook salmon to 690 mg Cu/L for blue tilapia Oreochromis aureus [17,18]. In the few tested marine fish larvae, these values ranged from 68 mg Cu/L for anchovy Engraulis japonicus to 1,800 mg Cu/L for sea bass Lates calcarifer [10,[19][20][21]. These results suggest that marine fish larvae might tolerate Cu exposure more than their freshwater counterparts.…”
Section: Acute Toxicity Of Coppermentioning
confidence: 87%
“…Experimental studies on heavy metals proved that they could impair the respiratory functions of the gills; consequently death in fish is probably caused by tissue hypoxia [11]. Metals affect not only the fish morphology, but also all biological activities [12]. Among the heavy metals; Cd and Pb are the serious heavy metals that produce histopathological alterations including liver damage [13], respiratory dysfunctions [14], testicular and ovarian alterations [15][16][17].…”
Section: Introductionmentioning
confidence: 99%